Direct Measurements of Torque During Holliday Junction Migration - Forth, Scott (The Biophysical Society, 2011)
DNA experiences torsional stress resulting from the activities of motor enzymes and bound proteins. The mechanisms by which this torsional stress is dissipated to maintain DNA structural integrity are not fully known. Here, we show that a Holliday junction can limit torsion by coupling rotation to translocation and torque to force. The torque required to mechanically migrate through individual junctions was found to be an order of magnitude smaller than that required to melt DNA. We also directly show that substantially more torque was required to migrate through even a single-base sequence heterology, which has important implications for the activity of junction-migrating enzymes.